Defining the Concept of Supply Chain Management and its Relevance to Romanian Academics and Practitioners - Mihai Felea; Irina Albăstroiu (Amfiteatru Economic Journal, 2013)
The purpose of this paper is to describe an extended approach to supply chain management by exploring some of the more prevalent Supply Chain Management definitions, frameworks and terminology. As regards the methodology of our study, should be noted that it was based on content analysis of the most important and popular definitions of the Supply Chain Management and associated terms, through a variety of secondary sources consisting of scientific papers and publications of professional organizations and practitioners. In our undertaking, we pursued the study and analysis of the above-mentioned concept's definitions, to set conceptual delimitations meant to clarify the extent of the Supply Chain Management concept, in the vision of both theorists and practitioners, but also to identify criteria/attributes depending on which has been defined over the years by both academics and business representatives, in order to propose new ways of defining the concept. Moreover, based on Romanian literature as reference, we took into consideration the presentation of the ways in which the term “Supply Chain Management” from English language was adopted and adapted to the Romanian language, which allowed us to identify the proper manner of transposing and defining the concept in the Romanian literature.
Keywords: M11; 330; supply chain management; supply chain; conceptual framework; logistics